The Russian economy under Putin - Becker, Torbjörn; Oxenstierna, Susanne 1956- (Routledge, 2019)
"This book presents a comprehensive view of the state of the Russian economy under President Putin. It considers the extent of Russia's integration in the world economy, where Russia's exports of oil and gas are a key factor, discusses Russia's internal challenges, including changing demographics, declining government revenue, the need to counter over-reliance on the oil and gas sector and the consequences of high military spending, and assesses the prospects for economic reform, highlighting especially the power struggles between different vested interests. Overall, the book provides a basis for understanding what has been going on in the Russian economy under President Putin and what the future may look like given the external environment, internal challenges and reform processes"--
Description based on print version record